2012
DOI: 10.1159/000345123
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological and Intelligence Evidence of Long-Distance Transit of Chemical Weapons Fallout from Bombing Early in the 1991 Persian Gulf War

Abstract: Background: Coalition bombings on the night of 18–19 January 1991, early in the Gulf War, targeted the Iraqi chemical weapons infrastructure. On 19 January 1991, nerve agent alarms sounded within Coalition positions hundreds of kilometers to the south, and the trace presence of sarin vapor was identified by multiple technologies. Considering only surface dispersion of plumes from explosions, officials concluded that the absence of casualties around bombed sites precluded long-distance transit of debris to US t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 28 publications
(15 reference statements)
0
30
0
Order By: Relevance
“…Figure 1 shows the central Kuwaiti theater of operations with chemical weapon research and production facilities, and military unit locations in January 1991 [23]. This was the setting during the first weeks of the Desert Storm conflict, which officially ended February 28, 1991.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 1 shows the central Kuwaiti theater of operations with chemical weapon research and production facilities, and military unit locations in January 1991 [23]. This was the setting during the first weeks of the Desert Storm conflict, which officially ended February 28, 1991.…”
Section: Resultsmentioning
confidence: 99%
“…This was the setting during the first weeks of the Desert Storm conflict, which officially ended February 28, 1991. Recent meteorological and intelligence data have provided support for more widespread troop exposure to chemical weapons during the conflict [23]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High arsenic levels in drinking water (>100μg/L) increased the risk of peripheral artery disease, coronary heart disease, stroke, and carotid atherosclerosis in studies conducted in Chile, 177 Taiwan, 178 Inner Mongolia, 179,180 Bangladesh, 181,182 and Pakistan. 183,184 The prospective cohort study from Bangladesh also examined the lower threshold of arsenic concentrations of arsenic in water and found that concentrations above 12 μg/L were associated with an increased hazard of CVD mortality.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%